Elemental Systematics in MORB Glasses From the Mid‐Atlantic Ridge. (5th November 2018) - Yang, Shuying; Humayun, Munir; Salters, Vincent J. M.
Abstract: In this study, a data set of 60 elements in 319 mid‐oceanic ridge basalt (MORB) glasses representing 144 chemically distinct lava flows from the Mid‐Atlantic Ridge was acquired by laser ablation inductively coupled plasma mass spectrometry. Our new data are comparable in terms of the number of elements analyzed to several recent MORB data sets, albeit limited in geographic coverage to the North Mid‐Atlantic Ridge. This extensive data set was used to examine the elemental systematics of depleted (D)‐, normal (N)‐, and enriched (E)‐MORBs. We show that elemental ratios sensitive to fluid transport in subduction zones (e.g., Th/U, Nb/U, Ba/Th, and Ba/La) are constant and similar to their primitive mantle values in N‐ and E‐MORBs, but depleted in accordance with their compatibility in D‐MORBs. The absence of evidence for subduction zone processing indicates the need to reassess the relation between MORB enrichment and recycled materials. Additionally, we reexamined the ratios of chalcophile and siderophile elements to lithophile elements of comparable compatibility, which are important in assessing planetary accretion, core formation, crust‐mantle differentiation, and hydrothermal ore formation processes. MORBs show significant negative anomalies of As, Tl, Pb, and Bi, but not of Sb, relative to lithophile elements of similar compatibility, which cannot be accounted for by melt depletion alone. The depletions of As, Tl, Pb, and Bi in MORB are complementary to significant enrichments observed in the continental crust, indicating that they have been transferred to the continental crust via fluid mobility in arcs or obduction of seafloor hydrothermal ores. Key Points: We present a new set of elemental analysis of 60 elements in 319 MORB glasses by LA‐ICP‐MS A recycled crustal origin for the enrichment of MORBs is not supported by elemental ratios sensitive to processing in the subduction factory All MORB glasses have identical depletions of As, Tl, Pb, and Bi, complementary to the continental crust acquired early in Earth history